2021
DOI: 10.1007/s10529-021-03117-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of the sheep pox virus structural protein SPPV117 in tobacco chloroplasts

Abstract: Objective A chloroplast transgenic approach was assessed in order to produce a structural protein SPPV117 of sheep pox virus in Nicotiana tabacum for the future development of a plant-based subunit vaccine against sheep pox. Results Two DNA constructs containing SPPV117 coding sequence under the control of chloroplast promoter and terminator of psbA gene or rrn promoter and rbcL terminator were designed and inserted into the chloroplast genome by a biolist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The RB70 insertion site has subsequently been commonly used in both biotechnology and basic research (e.g. Fuentes et al ., 2016; Krech et al ., 2013; Qu et al ., 2018; Ruf et al ., 2001, 2019; Stanbekova et al ., 2021; Wurbs et al ., 2007), including studies that yield exceptionally high transgene expression levels (Oey et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RB70 insertion site has subsequently been commonly used in both biotechnology and basic research (e.g. Fuentes et al ., 2016; Krech et al ., 2013; Qu et al ., 2018; Ruf et al ., 2001, 2019; Stanbekova et al ., 2021; Wurbs et al ., 2007), including studies that yield exceptionally high transgene expression levels (Oey et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Potential consequences of aadA insertion in the transplastomic RB70 line are of particular interest because the same insertion site (with identical direction of transgene expression) has been frequently used for diverse applications in basic research and chloroplast biotechnology (e.g. Fuentes et al ., 2016; Krech et al ., 2013; Qu et al ., 2018; Ruf et al ., 2001, 2019; Stanbekova et al ., 2021; Wurbs et al ., 2007). Our chloroplast ribosome profiling and transcriptome analyses revealed that not a single chloroplast gene displays significantly ( P value <0.05) or substantially (log 2 fold change >1 or <−1) altered expression in RB70 plants at either the level of transcript accumulation or ribosome coverage (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation